Improving Students' Literacy and Numeracy Skills Theme of My Obligations and Rights through Problem Based Learning Model for Grade 3 Students of SD Negeri 2 Ngalas in the 2022/2023 Academic Year - Suryani, Suryani (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This research aims to evaluate the impact of Problem-Based Learning (PBL) on improving the literacy and numeracy skills of third-grade students at SD Negeri 2 Ngalas, focusing on the theme "My Responsibilities and Rights" for the academic year 2022/2023. A total of 26 students participated in this research.The data analysis revealed a significant improvement in students' literacy skills after the implementation of PBL. The average initial literacy score of 67 increased to 74 post-PBL. A similar improvement was observed in numeracy skills, with the average initial score of 62 rising to 68. Statistical analysis confirmed that these differences were statistically significant.This study demonstrates the effectiveness of PBL in enhancing the literacy and numeracy skills of students within the context of the theme "My Responsibilities and Rights." The implementation of PBL provided students with opportunities for collaboration, critical thinking, and a better understanding of the concepts of responsibility and rights. Therefore, PBL emerges as a potential teaching method for enhancing literacy, numeracy, and social concept comprehension at the elementary school level.Future research is recommended to expand the sample size, include long-term monitoring, make comparisons with other teaching methods, and provide better teacher training in PBL design and implementation. These efforts will offer a more comprehensive understanding of the effectiveness of PBL in the context of primary education.